The New Role of Ulama in Nigeria: Focus on the Post 1999 Democratic Dispensation - Mukhtar Umar Bunza (Al-Jami'ah Research Centre, 2014)
Nigeria is a country with a centuries’ long tradition of Islamic revivalism and activism. It was the impact of the activities of the 17th century scholars of Nigeria that culminated in the success of the 19th century tajdeed movement that brought about the emergence of the muslim caliphate of Sokoto. British imperialism brought an end to the caliphate in the beginning of the 20th century, the circumstances of which have been consistently challenged mainly by the ulama and their followers ever since. Some contemporary scholars such as Shaikh Abubakar Mahmud Gummi, former Grand Qadi of Northern Nigeria, contributed significantly in the new dimension to the roles of muslim scholars in the government. Since 1999 muslim scholars have taken on new roles in the administration of states, serving as commissioners for newly established ministries for Religious Affairs, as special advisers, or directors of commissions like Hisbah, Hajj, Masjid, Moon Sighting, and other related government bodies, with full salaries and other benefits unlike ever before in the Nigerian system. This new role of ulama and its impacts in the governance of the contemporary Nigeria is what this paper intends to investigate and expound.[Nigeria merupakan sebuah negara dengan tradisi revivalisme dan aktivisme Islam selama berabad-abad. Hal itu terkait dengan upaya para ulama Nigeria abad ke-17 yang berpuncak pada keberhasilan gerakan tajdid pada abad 19 dengan munculnya kekhalifahan muslim dari Sokoto. Imperialisme Inggris mengakhiri kekhalifahan ini pada awal abad ke-20, yang terus dilawan oleh terutama para ulama secara konsisten. Beberapa ulama kontemporer seperti Syaikh Abubakar Mahmud Gummi, mantan Grand Qadi Nigeria Utara, memberikan kontribusi signifikan dalam membentuk dimensi baru peran ulama dalam pemerintahan Nigeria modern. Sejak tahun 1999 para ulama telah mengambil peran baru dalam pemerintahan, sebagai pegawai Kementerian Agama yang baru didirikan, sebagai penasihat ahli, atau direktur komisi seperti Hisbah, Haji, Masjid, Rukyah Hilal, dan badan-badan pemerintah terkait lainnya, dengan gaji penuh. Peran baru dari ulama dan pengaruhnya dalam pemerintahan Nigeria kontemporer inilah yang menjadi fokus tulisan ini.]